Perilaku 5M Pencegahan COVID-19 pada Masyarakat Usia 19-45 Tahun - Safitri, Yusfina Rachma Dayu; Indarjo, Sofwan (Center for Public Health Nutrition Studies, Universitas Negeri Semarang, Indonesia, 2023)
Background: Until November 28, 2021 in Wadaslintang Village there were 186 COVID-19 cases and 71 cases (38.17%) were age 19-45 years. This age has the potential to be infected and become a silent carrier, so it is necessary to implement 5M, but 5M has not been fully implemented by the community. This study aims to determine the factors related to the 5M behavior of preventing COVID-19 in community age 19-45 years. Methods: This type of research is observational analytics with a cross sectional design. The sample size is 328 which was taken using the Proportional Random Sampling. Data collection was carried out using a questionnaire. Data were analyzed using chi square test (α=0.05). Results: The research showed that gender (p-value<0.001), education level (p-value<0.001), employment status (p-value=0.200), level of knowledge (p-value<0.001), perceived vulnerability (p-value<0.001), perceived seriousness (p-value<0.001), perceived benefits (p-value=0.003), perceived barriers (p-value<0.001), access to information (p-value=0.000), family support (p-value<0.001), and community support (p-value<0.001). Conclusion: There is relation between gender, level of education, level of knowledge, perceived susceptibility, perceived severity, perceived benefit, perceived barrier, access to information, family support, and community support with 5M behavior to prevent COVID-19 in community age 19-45 years in Wadaslintang Village.